Reconsidering place branding: "connecting the dots" between placemaking, policy making and sustainable development - Laura Reynolds (Welsh Economic Review (WER), 2021)
This article sets out developments in the place branding literature, detailing its potential to support sustainable development when considered as a process that reflects and supports the place and its people, policies and practices. To achieve these aims, it is suggested that a greater unison of place branding and placemaking needs to occur, supporting the ongoing involvement of people in the shared (re)invention of lived-in places. Both of which benefit from collaborations and partnerships with stakeholders, helping to (re)create and (re)present the places in which they live, work, visit, and invest in. Building on these assumptions, this article looks at how placemaking and place branding are interwoven into the Well-being of the Future Generations (Wales) Act 2015, which provides the legislative and policy backing to enact substantive change and support sustainable development in Wales. Based on reflections of the Act and the Future Generation Report (2020) this paper proposes that policy making can help to bring together placemaking and place branding, and when all three components are pursued collectively and in unison they can bring about substantive economic, social, cultural and environment benefits.
Keywords: 330; Nachhaltige Entwicklung; Standortmarketing; Bürgerbeteiligung; Regionalpolitik; Wales